Safety, health and environment hazard control in a Malaysian performing arts theatre production / Charlene Angela J.N. Sundraraj - Charlene Angela, J.N. Sundraraj (2018)
This research identifies and investigates the Safety, Health and Environment Hazards in a Malaysian Performing Arts Theatre Production. It analyses and quantifies the likelihood and severity of hazards on the well-being of theatre practitioners and members of the public and ascertains measures to prevent the risks. This research is important due to the current lack of regulations on the Malaysian performing arts theatre industry while operating under limited resources. It also seeks to build Safety, Health and Environment data for the Malaysian performing arts theatre industry. Currently, there is no official risk assessment on the production work of small scale Malaysian theatre production companies. As the production process begins with pre-production and production work outside of the theatre, the gap in research on hazards of these work processes are closed using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method on a Malaysian theatre company. The Malaysian company studied is a theatre company that specialises in opera productions with cast members, orchestra, production workers, designers and children. The performance was held at a theatre located in Kuala Lumpur, Malaysia. Each phase of the production was separated according to job steps by location, and hazards were identified accordingly. Each hazard was assigned a risk level according to likelihood and severity and control measures were identified to prevent these risks. It was found that most of the risks faced at the rehearsal space and the theatre were moderate, followed by imminent risk and insignificant risk. At the theatre, the percentage of moderate, imminent and insignificant risks were 64%, 35% and 1% respectively. At the rehearsal space, the risks were 80%, 19% and 2% respectively. Steps to prevent and mitigate the risks were highlighted in the form of recommendations to be shared with theatre practitioners and implemented in the theatrical production process.